Association of Polish Electrical Engineers and the Chamber of Licensed Experts - Maria Zastawny; Andrzej Skorupski; Ryszard S. Romaniuk (International Journal of Electronics and Telecommunications, 2024)
At the beginning of the year 2024, 65 years will have passed since the establishment of the Chamber of Experts of the Association of Polish Electrical Engineers (SEP). During this period, SEP underwent significant changes. Particularly serious changes in the conditions for practicing association expertises have occurred in recent years, along with dynamic economic and political changes in Poland. Expertise is strongly based on economic conditions and the ways in which scientific, technical and industrial competences are expanded and available in the society. In the past, these highest competencies were quite strictly limited to well-organized professional communities related to scientific and technical associations such as SEP, and federal bodies such as NOT. Competencies were also generated in the best industrial centres associated with academic polytechnic centres. Today the role of expertises in electrical, electronics and ICT engineering is undergoing significant changes.